Juridical Analysis of Investor Default Cases with CV Business Entities Related to Cooperation Agreement Letters (Decision 55/Pdt Gs/2022/PN Sby) - Deviana Axfelia; Gunardi Lie; Moody Rizqy Syailendra Putra (CV. Rayyan Dwi Bharata, 2023)
Basically an agreement is made based on negotiations by the parties, but using standard clauses. One of the default cases that occurred was decided by the Surabaya District Court at the First Level Court with case number 55/Pdt GS/2022/PN Sby. The lawsuit was filed because the Defendant, namely CV AL-FAYYADH, had defaulted on the Plaintiff who is an investor/financier. The method in this study uses normative juridical methods. defaults made by CV AL-FAYYADH did not carry out achievements in payment. The dispute resolution process between CV AL-FAYYADH and Investors used the negotiation route based on Article 6 paragraph (2) of Law Number 30 of 1999 concerning Arbitration and Alternative Dispute Resolution by producing a new agreement or renegotiation and of course with a favorable agreement before going through the courts.